Costa Rica-Panama arbitration: memorandum on uti possidetis (1913)
In the discussion of the pending question, much prominence has at times been given to the subject of uti possidetis. Especially is this the case with the arbitration before the President of France, in which the representatives of Colombia (predecessor of Panama) endowed the phrase with an importance altogether factitious, making it, indeed, in the form of the uti possidetis juris, the very foundation of their argument. This was all the more remarkable, because the words uti possidetis, as we shall hereafter more fully show, nowhere occur in the treaties between the two countries. Nevertheless, the use which has been made of the phrase renders it necessary to present the matter in its various aspects.